Upcoming: Piloting a Community-Based Learning Teaching Assistant Program - Bethany Ozorak; Sascha Goluboff (Journal of the Scholarship of Teaching and Learning)
Research indicates that student leadership and peer-to-peer mentoring enhance the high-impact practice of student service-learning. This article explores the successful implementation of a community-based learning teaching assistant program by a community-engaged office at a four-year liberal arts institution. It discusses the program's development, curriculum goals, outcomes, and limitations. The steps involved in this process are adaptable, making the implementation of such a program practical for higher education staff and faculty interested in expanding their community engagement work and leadership opportunities.